2022
DOI: 10.3389/fpsyt.2022.834753
|View full text |Cite
|
Sign up to set email alerts
|

One Year Facing COVID. Systematic Evaluation of Risk Factors Associated With Mental Distress Among Hospital Workers in Italy

Abstract: IntroductionItaly was the first Western country affected by the COVID-19 pandemic that still constitutes a severe challenge for healthcare workers (HCWs), with a deep impact on their mental health. Several studies confirmed that a considerable proportion of HCW developed adverse psychological impairment (PsI). To focus on preventive and rehabilitation measures, it is fundamental to identify individual and occupational risk factors. We systematically assessed possible PsI among all employees in a large universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 38 publications
2
15
1
Order By: Relevance
“…209 articles continued to the full text screening stage, of which 119 studies were selected for inclusion in our meta-analysis with a total of 117,143 participants ( Table 1A ). All 119 studies were cross-sectional observational studies ( Agberotimi et al., 2020 ; Alah et al., 2021 ; Ali et al., 2020 , 2022 , 2021 ; Alonso et al., 2021 ; Alshehri and Alghamdi, 2021 ; Asnakew et al., 2021 ; Ayalew et al., 2022 ; Azoulay et al., 2021 ; Bassi et al., 2021 ; Benzakour et al., 2022 ; Bizri et al., 2022 ; Bonzini et al., 2022 ; Bulut et al., 2021 ; Caillet et al., 2020 ; Caliandro et al., 2022 ; Carmassi et al., 2022 , 2021a , 2021b ; Chang et al., 2022 ; Chan et al., 2021 ; Chatzittofis et al., 2021 ; Chaudhary et al., 2021 ; B. Chen et al., 2022 ; Cheng et al., 2020 ; Chen et al., 2021 ; Chew et al., 2020 ; Chowdhury et al., 2021 ; Civantos et al., 2020a , 2020b ; Cortés-Álvarez and Vuelvas-Olmos, 2020 ; Costantini et al., 2022 ; Crowe et al., 2022 ; Demartini et al., 2020 ; Dobson et al., 2021 ; Dykes et al., 2022 ; Ergai et al., 2022 ; Essadek et al., 2022 ; Fattori et al., 2021 ; Geng et al., 2021 ; Gilleen et al., 2021 ; Gorini et al., 2020 ; Guo et al., 2021 ; Hajure et al., 2021 ; Hasanvandi et al., 2022 ; Honarmand et al., 2022 ; Hong et al., 2021 ; Huarcaya-Victoria et al., 2022 ; …”
Section: Resultsmentioning
confidence: 99%
“…209 articles continued to the full text screening stage, of which 119 studies were selected for inclusion in our meta-analysis with a total of 117,143 participants ( Table 1A ). All 119 studies were cross-sectional observational studies ( Agberotimi et al., 2020 ; Alah et al., 2021 ; Ali et al., 2020 , 2022 , 2021 ; Alonso et al., 2021 ; Alshehri and Alghamdi, 2021 ; Asnakew et al., 2021 ; Ayalew et al., 2022 ; Azoulay et al., 2021 ; Bassi et al., 2021 ; Benzakour et al., 2022 ; Bizri et al., 2022 ; Bonzini et al., 2022 ; Bulut et al., 2021 ; Caillet et al., 2020 ; Caliandro et al., 2022 ; Carmassi et al., 2022 , 2021a , 2021b ; Chang et al., 2022 ; Chan et al., 2021 ; Chatzittofis et al., 2021 ; Chaudhary et al., 2021 ; B. Chen et al., 2022 ; Cheng et al., 2020 ; Chen et al., 2021 ; Chew et al., 2020 ; Chowdhury et al., 2021 ; Civantos et al., 2020a , 2020b ; Cortés-Álvarez and Vuelvas-Olmos, 2020 ; Costantini et al., 2022 ; Crowe et al., 2022 ; Demartini et al., 2020 ; Dobson et al., 2021 ; Dykes et al., 2022 ; Ergai et al., 2022 ; Essadek et al., 2022 ; Fattori et al., 2021 ; Geng et al., 2021 ; Gilleen et al., 2021 ; Gorini et al., 2020 ; Guo et al., 2021 ; Hajure et al., 2021 ; Hasanvandi et al., 2022 ; Honarmand et al., 2022 ; Hong et al., 2021 ; Huarcaya-Victoria et al., 2022 ; …”
Section: Resultsmentioning
confidence: 99%
“…with scores above the cut-off in at least one scale among GAD-7, IES-R and GHQ-12). Results obtained from the analysis of risk factors for psychological impairment, measured through the above-mentioned scales, are presented in details in a previous paper (Bonzini et al, 2022). GHQ-12 proved to be and effective screening tool since it was able to determine whether a subject required further evaluation through the second-level questionnaire.…”
Section: Preliminary Resultsmentioning
confidence: 99%
“…Previous research has also indicated increased symptoms of anxiety and depression among healthcare workers during the COVID-19 pandemic [ 24 , 25 ]. The prevalence rate for anxiety symptoms reported in previous studies varied between 11.7% and 50% [ 24 , 26 ], while those observed for depression were between 13.7% and 42% [ 27 , 28 , 29 ]. The differences in rates across studies may have resulted from the characteristics of the course of infections in a given country, the conditions of the healthcare system, the precise moment of the pandemic when the study was carried out, and the measurement tools used.…”
Section: Discussionmentioning
confidence: 98%